Intra-rater and Inter-instrument Reliability on Range of Movement of Active Knee Extension - Germanna de Medeiros Barbosa; Glauko André de Figueirêdo Dantas; Bianca Rodrigues da Silva; Scheila Marisa Pinheiro; Heleodório Honorato dos Santos; Wouber Hérickson de Brito Vieira
Abstract The objective of the present study was to evaluate the reliability of intra-rater and inter-instrument measures during two flexibility programs. Fifty-three active and healthy males, aged between 18 and 28 years old, were randomly included in three groups: control (Cg, n = 18), static stretching (SSg, n = 17), and dynamic stretching (DSg, n = 18). All participants underwent measurements of their active range of knee extension using manual goniometry and computerized photogrammetry, measured in four separated assessments and analyzed using the SPSS, with ((5%. Both methodologies presented very strongintra-raterreliability (ICC: 0.91(0.99; P<0.001) at all four assessments in all the groups, and the instruments showed weak (r: 0.31-0.6) to strong(r: 0.61-0.9) correlation, in the Cg (P<0.05) and strong (r: 0.61-0.9) in the SSg and DSg (P<0.01), although without differences between groups, indicating that the measures are equally reliable, regardless of interventions.